Identifying the protein interactions of Mre11-Rad50 in Haloferax volcanii during double-strand break repair - Wickham-Smith, Charlie (2015)
The Mre11 and Rad50 proteins are found in all domains of life and form a complex that locates and binds to DNA double-strand breaks (DSBs). The complex tethers DNA ends and coordinates the repair of DSBs. In Haloferax volcanii, mre11rad50 mutants are more resistant to DNA damage than the wild-type. Mre11-Rad50 is believed to restrain repair of DSBs by homologous recombination (HR) while other repair pathways can operate. Mutants of mre11rad50 cannot utilise this restraining mechanism so HR is believed to solely repair DSBs, leading to an increase in DNA damage resistance. H. volcanii is highly polyploid, possessing up to 20 copies of its genome. This restraining method of repair will prevent DNA ends engaging with multiple partners, which could be highly toxic. The specific details of how H. volcanii repair DSBs are unknown, including the protein interaction of Mre11-Rad50.